Cornual Polyps of the Fallopian Tube Are Associated with Endometriosis and Anovulation - S. A. AlAsiri; M. Ghahremani; P. F. McComb (Obstetrics and Gynecology International)
Background. The relationship between tubal cornual polyps and endometriosis and ovulatory disorders in infertile women is unclear. Our objective was to determine such an association from our database and review the literature. Methods. Twenty-two infertile women with tubal cornual polyps were assessed for coexistence of oligoovulation/anovulation and endometriosis with stratification for polyp diameter (large: ≥5 mm diameter, small <5 mm diameter). Result(s). Oligoovulation/anovulation was more prevalent in women with large versus small tubal cornual polyps (P=0.0048). Endometriosis was associated with both large and small polyps. Conclusion(s). This case series confirms the association of tubal cornual polyps with oligoovulation/anovulation and endometriosis in infertile women. This case series is limited by a lack of controls.